Determinan Kemiskinan Multidimensi Perempuan Berusia Produktif di Pulau Papua Tahun 2020 - Faricha Zahara AlChasanah; Ekaria Ekaria (Seminar Nasional Official Statistics, 2022)
Poverty is problem for many countries, including Indonesia. In Indonesia, women experience poverty more severely than men. Papua Island was chosen as the research locus because it is consistent with the highest poverty rate. Measuring poverty with a monetary approach is not considered ideal, so the research focuses on measuring multidimensional poverty. This study aims to find out the general description and variables that are thought to influence the multidimensional poverty women of productive age in Papua Island 2020 based on social, demographic and economic aspects by taking into account inter-regional linkages. The data used are Susenas KOR and KP in 2020 and the method of spatial regression analysis with the Spatial Error Model. The results showed that 70.3532 percent women of productive age in Papua Island 2020 experienced multidimensional poverty, with a higher percentage experienced by Papua Province in the districts, especially Deiyai, Nduga and Intan Jaya. The variables that affect the multidimensional poverty women of productive age in Papua Island 2020 are the percentage of villages/kelurahan with rural status and women's economic and technological conditions.